2011
DOI: 10.1155/2011/847835
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Care Usage by HIV-Positive Patients in the HAART Era

Abstract: In the 1980s the outlook for patients with the acquired immunodeficiency syndrome (AIDS) and critical illness was poor. Since then several studies of outcome of HIV+ patients on ICU have shown improving prognosis, with anti-retroviral therapy playing a large part. We retrospectively examined intensive care (ICU) admissions in a large HIV unit in London. Between April 2001 and April 2006 43 patients were admitted to the ICU. The mean age of patients was 44 years and 74% were male. Fifty-six percent of admission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
18
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 27 publications
6
18
2
1
Order By: Relevance
“…This result contradicted data from other studies, where elevated APACHE-II scores were prognostic of adverse outcomes in these patients [5, 9, 10, 12]. Interesting is the high number of patients who received mechanical ventilation in this study, outweighing results from other reports [911, 13, 14, 20, 23, 28]. However, our patients' length of stay in ICU is comparable to figures shown previously [11, 14, 18, 27].…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…This result contradicted data from other studies, where elevated APACHE-II scores were prognostic of adverse outcomes in these patients [5, 9, 10, 12]. Interesting is the high number of patients who received mechanical ventilation in this study, outweighing results from other reports [911, 13, 14, 20, 23, 28]. However, our patients' length of stay in ICU is comparable to figures shown previously [11, 14, 18, 27].…”
Section: Discussioncontrasting
confidence: 96%
“…Although comparable to results from other similar studies [12, 14, 27], the median CD 4 cell count in our patients was higher than those reported in other series [9, 10, 13, 28]. A large proportion of our HIV-infected population is known for poor adherence to antiretrovirals and ongoing substance abuse.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…97,98 Acute respiratory failure has remained the most common cause for ICU admissions in patients with HIV, and pneumonia is the overall leading cause of ARDS. [99][100][101] Streptococcus pneumonia is the most frequent bacteria isolated, followed by Hemophilus influenzae and Staphylococcus aureus. 102 In addition, Pseudomonas aeruginosa and Enterobacteriaceae spp are important considerations.…”
Section: Acute Respiratory Distress Syndrome In Patients Infected Witmentioning
confidence: 99%